The performance comparison of the open-ended fund and close-ended fund in Pakistan - Ahmad, N. (2020)
This research study show performance comparison of the Net Asset Values (NAVs) return of Open-ended and Close-ended mutual funds in Pakistan. The aim of the study to analyze the dissimilarity between the “net asset values” (NAVs) returns of the open-ended and close-ended mutual funds. The monthly data of Net Asset Value return of both open-ended funds and close-ended funds were taken over the period from 2006 till 2011 (inclusive). The NAVs return was computed through (LN) natural log function. The normality test was conducted initially and then the Kolmogorov-Smirnov and Shapiro-Wilk test were applied, their result showed that the data is not normally distributed. The Mann- Whitney U test and then further the Kruskal Wallis was conducted to check for the differences between these two groups of independent variables. It showed dissimilarity between the net asset value returns of the open-ended and close-ended mutual funds. Further Kruskal Wallis test results indicated significant differences between the open-ended and close-ended funds. It is concluded that the performance of open-ended and close-ended mutual funds is not the same. Also, growth is witnessed in the mutual fund industry and many close-ended funds have been converted to open-ended funds.